Understanding food systems drivers: A critical review of the literature - Béné, Christophe; Prager, Steven D.; Achicanoy Estrella, Harold Armando; Álvarez Toro, Patricia; Lamotte, Lea; Bonilla Cedrez, Camila; Mapes, Brendan Robert (Elsevier, 2019)
• A critical review on food systems drivers is conducted. • The review reveals several methodological and conceptual issues. • Twelve major global drivers are identified through an inductive analysis. • The links between those drivers and food systems' transitional changes are discussed. • Drivers' impacts appear highly country specific and any global trend difficult to estimate empirically.